SECURITY IN INTERNATIONAL TOURISM AS A FACTOR OF SUSTAINABLE DEVELOPMENT - Атаманчук, Зорина; Тимчишин, Юлия (SWorldJournal, 2021)
The article has clarified the place and role of tourism in achieving 17 goals of sustainable development. It is substantiated that the implementation of the goals and tasks will enable tо direct the аctivity of the world community through the development